2015
DOI: 10.1002/ppap.201500061
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Plasma‐treated Organic Surfaces and Plasma Polymers by Secondary Ion Mass Spectrometry

Abstract: This feature article is focused on the application of secondary ion mass spectrometry (time-offlight SIMS) to the chemical and structural study of plasma-treated organic surfaces and plasma polymer films. After a brief historical perspective and a presentation of the recent developments of SIMS, illustrative case studies involving plasma-treated polymer surfaces and plasma polymers are presented. Beyond surface analysis by static SIMS, we show the potential of molecular depth-profiling by low-energy Cs þ ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…[25][26][27][28] Recently, first time-of-flight SIMS (ToF-SIMS) studies were demonstrated to be promising for the in-depth characterization of plasma polymer multilayers or gradients. 29 Here, amino-and carboxylic acid-based polymers -of general interest for the design of bio-interfaces, 30,31 are considered. Various film designs including bilayers and microstructured films are presented.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Recently, first time-of-flight SIMS (ToF-SIMS) studies were demonstrated to be promising for the in-depth characterization of plasma polymer multilayers or gradients. 29 Here, amino-and carboxylic acid-based polymers -of general interest for the design of bio-interfaces, 30,31 are considered. Various film designs including bilayers and microstructured films are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with principal component analysis (PCA), secondary ion mass spectrometry (SIMS) has proven to be a powerful method to determine the structure of plasma polymers and, in particular, to determine their crosslinking degree . Plasma polymers form very thin layers (<1 μm) with a complex crosslinked structure, and therefore, SIMS is one of the few tools able to access the chemical information …”
Section: Introductionmentioning
confidence: 99%
“…In the plasma literature, a popular procedure for the surface characterization of plasma‐modified polymers is reported, that combines XPS (information about elements and chemical bonds), WCA (wettability of the surface related to the new grafted functionalities), and AFM (morphology) . In this context, ToF‐SIMS is an excellent complement, indispensable to elucidate the structural and chemical modifications of plasma‐treated polymers, not only at the surface (via the mass spectra), but also along the depth (via the molecular depth‐profiles) . The latter was recently possible using large argon gas cluster ion beams (GCIB) for sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] In this context, ToF-SIMS is an excellent complement, indispensable to elucidate the structural and chemical modifications of plasma-treated polymers, not only at the surface (via the mass spectra), but also along the depth (via the molecular depthprofiles). [15] The latter was recently possible using large argon gas cluster ion beams (GCIB) for sputtering. In these beams, each Ar n þ ion projectile is constituted by hundreds to thousands of atoms (n) and possesses an energy of few keV.…”
Section: Introductionmentioning
confidence: 99%